Aspects of the spatial and behavioural ecology of Hippopotamus amphibious in the Saint Lucia Estuary, KwaZulu-Natal, South Africa - Prinsloo, Alexa Simone (Department of Biological Sciences, 2016)
The common hippopotamus (Hippopotamus amphibius) is endemic to Africa but threatened by range restriction, exploitation and competition with humans and domestic livestock for access to critical resources such as fresh water and grazing. Collectively these impacts have resulted in population declines throughout most of their range with the consequence that hippos are classified as Vulnerable on the IUCN Red list. Despite these threats to their persistence and their important ecological role as ecosystem engineers there have been surprisingly few studies concerning factors that influence their current distribution and habitat use. Such research is important for developing effective conservation and management plans to improve the protection of vulnerable and ecologically important species such as hippo. South Africa is home to one of a few growing hippo populations and one of the last persisting in an estuarine habitat. The St Lucia Estuary, one of three Ramsar Wetlands of International Importance located in the iSimangaliso Wetland Park (itself a UNESCO World Heritage site), in northern KwaZulu-Natal is not only the largest estuarine system in Africa, but is also home to one of South Africa's largest hippo populations. In this study I explore aspects of the spatial and behavioural ecology of hippo within the St Lucia Estuary. More specifically, I investigate select abiotic and biotic predictors of hippo presence and the frequency with which they return to their diurnal lie-up sites. I used binary logistic regression models to evaluate the effects of the selected habitat features on hippo occurrence at two spatial scales (broad and fine). I used a negative binomial with log-link model to evaluate the effects of the selected habitat features on the frequency of use of sites (hippo persistence) in the fine-scale study. In addition, I employed both instantaneous scan sampling and continuous sampling methods in an attempt to determine the diurnal activity budgets and social interactions of a single group near the mouth of the St Lucia Estuary. I used non-parametric tests to evaluate differences in behaviour with daytime and across sampling days with a view to an improved understanding of how the environment influences the behaviour of hippo in an environment subject to ongoing human modification.